The Effect of Product Innovation and Product Quality on Competitive Advantage - Rizky Desyanti Fauziah; Ari Arisman; Depy Muhamad Pauzy (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
This study aimed to determine the effect simultaneously and partially of the product innovation and product quality on competitive advantage in UMKM Mukena Embroidery Aiwawardrobe, Sukaraja District, Tasikmalaya Regency. The method used in this study is a causal method with a quantitative approach to employees with a sample of 110 respondents. The data collected in the form of primary data. Multiple regression equation data analysis, multiple correlation analysis, coefficient of determination analysis using SPSS software. The results of this study indicate that product innovation and product quality simultaneously have a significant effect on competitive advantage in UMKM Mukena Embroidery Aiwawardrobe, Sukaraja District, Tasikmalaya Regency. Product innovation partially has a significant effect on the competitive advantage of Mukena Embroidery Aiwawardrobe, Sukaraja District, Tasikmalaya Regency. Product quality partially has a significant effect on competitive advantage in Mukena Embroidery Aiwawardrobe, Sukaraja District, Tasikmalaya Regency.